Perilaku nyamuk anopheles punctulatus dan kaitannya dengan epidemiologi malaria di desa Dulanpokpok Kabupaten Fakfak, Papua Barat - G. Saputro .; U. Kesumawati Hadi; FX. Koesharto . (Hemera Zoa, 2010)
Malaria is a major health problem in Fakfak District. The studies were aimed to discribe the behavior of Anopheles punctulatus, the biting activities, the characteristics breeding place, the incidence rate of malaria, and the people behavior in Dulanpokpok Village. The studies were done from May to August 2009. The Anopheles mosquitoes were collected by indoor and outdoor human landing collection in the evening between 6 pm and 6 am. Breeding place characteristics were measured based on the larval collections. The people behavior were interviewed with indepth inteview. The result showed that the man biting rate of A. punctulatus indoors was 1,38 bites/man/night, and outdoors was 1,48 bites/man/night. The biting activities of A. punctulatus were known pools, wheel ruts, ditches and puddles. The breeding places characteristic of A. punctulatus were water base an mud, water depth 5-50cm, water temperature 28°C , pH 6-6,8, and sality 0%. The lack of knowledge and the behavior of people going outdoor during the night will increase the risk of malaria infection in the study area.